Frontline Employees’ Motivation towards Customers’ Value Outcomes: A Context of Non-Fuel Retailing - Muhammad Farrukh Abid; Muhammad Nawaz; Junaid Siddique; Satirenjit Kaur Johl; Muhammad Aamir Nadeem; Muhammad Mazhar (Jurnal the Messenger, 2024)
Introduction: The present study aimed to explore the frontline employees in-shop motivation to influence the customers in-shop emotions. The study further proposed the conceptual foundations of the dynamic nature of value outcomes in non-fuel retail stations, where each customer perceives the interaction with frontline employee differently. Therefore, the value outcomes based on the customers’ in-shop emotions were dynamic.